`Same sport, different game`: male and female junior Norwegian national ice hockey players` perceptions of their talent development environments - Bergström, M.; Mehus, I.; Aspvik, N. P.; Høigaard, R.; Sæther, S. A. (Sport in Society: Cultures, Commerce, Media, Politics, 2026)
Women`s ice hockey has experienced rapid changes in the last decades. Nevertheless, there is still a gap in the preconditions between male and female players. The aim of the present study was to explore how Norwegian junior ice hockey players perceive their talent development environments (TDEs) and view their future athletic career. In total, ten female and ten male players participated in qualitative focus group interviews. The results show that female and male players perceive their TDEs and future career prospects differently. Compared to male players, female players perceived less support and a lack of competition. Furthermore, while male players internalized a singled-minded focus on sport to become professional athletes, the female players viewed a professional career as unrealistic. Continued work on improving the TDEs for female ice hockey players and their opportunities to play professionally is necessary to make ice hockey more gender equal.